Peranan Guru terhadap Psikis Peserta Didik Perilaku Bulliying di SDN 173682 Desa Siregar Kabupaten Toba - Ginting, Nurlia; Saragih, Rayani; Panjaitan, Nurhayati M; Sihite, Cici Sriwilina; Laia, Viktor Riusman (EDUPEDIA Publisher, 2024)
Bullying is an act of oppression or violence carried out by a person or group of people to hurt or corner other people. Bullying can happen to anyone, but is more often done by teenagers. There are several impacts of bullying that need to be aware of because they can affect the mental health of victims and perpetrators, such as triggering emotional disorders, mental problems, sleep disorders, decreased performance, and so on. Psychological violence in question can take the form of: exclusion, rejection, neglect, humiliation, spreading rumors, mocking calls, intimidation, terror, public humiliation, blackmail; and/or, other similar acts. Bullying is physical violence and/or psychological violence as explained previously, which is carried out repeatedly because of unequal power relations. The Impact of Bullying on Victims If it is not stopped immediately, bullying behavior can cause various kinds of mental and physical disorders for victims who experience it, such as: Triggering Mental Problems. The most frequent impact of bullying on victims is triggering mental health problems, such as anxiety disorders, depression, and post-traumatic stress disorder (PTSD). The effect of bullying on mental health is usually experienced by victims over a long period of time. Sleep disorders Insomnia is also one of the impacts of bullying on victims that should not be underestimated. The reason is, victims of bullying often experience prolonged stress which can cause hyperarousal, namely a condition when the body becomes very alert, disrupting the balance of the sleep and wakefulness cycle. Decreased Achievement Children who experience bullying will usually have difficulty focusing and concentrating while studying. Victims of bullying also often feel reluctant to go to school because they want to avoid the bullying they experience. If left to continue, this condition can have an impact on reducing the child's academic performance. Having Thoughts of Revenge The next impact of bullying on the victim's psychology is having thoughts of revenge. This needs to be watched out for because it can cause someone to commit acts of violence against other people to vent their frustration.